Building websites with e107 a step-by-step tutorial to getting your e107 website up and running fast - Boomer, Theodore S.; Safari eBooks (Birmingham, U.K. : Packt Pub., 2007)
"e107 is a PHP-based content management system that uses the popular open source MySQL database system for content storage. e107 is released under the terms of the GNU General Public License and is completely free, totally customizable and in constant development. It is an ideal tool for developing small to large dynamic community websites, intra company portals, corporate portals, weblogs and much more. It has a large, enthusiastic, and helpful community of users."--Resource description page.
Description based on print version record.
Includes index.
Keywords: Web site development; Web sites -- Authoring programs; MySQL (Electronic resource); Internet programming; Electronic books